Metal-doped Cu-Si-based catalyst as well as preparation method and application thereof

By loading Cu elements and doped metal elements in situ on Si powder, forming a metal-doped Cu-Si-based catalyst, the problems of low purity and high energy consumption in the preparation process of trichlorosilicon in the prior art are solved, and a more efficient catalytic reaction is achieved.

CN119524854APending Publication Date: 2025-02-28WUHAN INST OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411664287.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The selective effect of the by-product SiCl4 in the existing trichlorosilicon preparation process is caused by the limitation of the purity of trichlorosilicon, and the catalyst particle size is large and the reaction energy consumption is high.

Method used

A metal-doped Cu-Si-based catalyst with a flower-like high pore spherical structure is formed by using microemulsion freeze-drying and azeotropic distillation coupled with microwave-assisted microwave-assisted processes by loading Cu elements and doped metal elements on Si powder in situ.

Benefits of technology

The catalytic reaction temperature is reduced, the catalyst usage is reduced, and the reaction selectivity and yield of trichlorosilicon are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005144218370000011
    Figure HDA0005144218370000011
  • Figure HDA0005144218370000012
    Figure HDA0005144218370000012
  • Figure HDA0005144218370000013
    Figure HDA0005144218370000013
Patent Text Reader

Abstract

The invention discloses a preparation method of a metal-doped Cu-Si-based catalyst. The preparation method comprises the following steps: 1) uniformly mixing copper salt and metal additive salt in a polar solvent to prepare a composite metal salt solution; 2) uniformly mixing with a non-polar organic solvent and a surfactant to form a stable micro-emulsion system, and freezing to obtain a stable micro-emulsion; 3) adding a carbon source precursor into the microemulsion for azeotropic distillation reaction, washing and freeze-drying to obtain composite powder; and 4) uniformly dispersing the obtained composite powder and Si powder in a polar solvent to obtain an aerosol precursor solution, and then performing atomization, microwave treatment, drying and calcination to obtain the metal-doped Cu-Si-based catalyst. According to the invention, effective loading and highly uniform dispersion of auxiliary metal M and Cu elements on the Si powder can be realized, and when the Si powder is applied to preparation of trichlorosilane, reduction of catalytic reaction temperature, reduction of catalyst dosage, improvement of reaction selectivity and improvement of trichlorosilane yield are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysis, and in particular relates to a metal-doped Cu-Si based catalyst and a preparation method and application thereof. Background Art

[0002] Trichlorosilane is an important organic silicon monomer material, which is widely used in various fields. Especially in the fields of photovoltaic solar energy and semiconductor chips, trichlorosilane, as an important reaction gas, plays an important role in the growth of silicon epitaxial wafers. It is urgent to develop a suitable catalyst and preparation method for trichlorosilane.

[0003] At present, the preparation process of trichlorosilane gas usually adopts the silicon chlorination method, which uses silicon powder and hydrogen chloride to react in a fluidized bed or fixed window. The reaction temperature is about 300°C, and Cu or Fe is usually added as a catalyst to improve the conversion rate and selectivity. However, the selectivity of the existing trichlorosilane preparation process is mainly affected by the by-product SiCl4, which limits the purity of trichlorosilane to a certain extent; in addition, there are also problems such as the large size of the catalyst particles of the prepared trichlorosilane and high reaction energy consumption. Summary of the invention

[0004] The main purpose of the present invention is to provide a Cu-Si based catalyst doped with an auxiliary metal M in situ, in view of the deficiencies in the prior art, to achieve effective loading and highly uniform dispersion of the auxiliary metal M and Cu on Si powder, and to apply the catalyst to the preparation of trichlorosilane, thereby helping to reduce the catalytic reaction temperature, reduce the amount of catalyst used, improve the reaction selectivity, and improve the trichlorosilane yield.

[0005] To achieve the above, the technical solution adopted by the present invention is:

[0006] A method for preparing a metal-doped Cu-Si based catalyst comprises the following steps:

[0007] 1) uniformly mixing copper salt and metal auxiliary salt in a polar solvent to obtain a composite metal salt solution;

[0008] 2) mixing the composite metal salt solution, the non-polar organic solvent and the surfactant uniformly to form a stable microemulsion system, and then freezing the system to obtain a stable microemulsion;

[0009] 3) adding the carbon source precursor to the microemulsion obtained in step 2) to carry out azeotropic distillation reaction, and then washing and freeze-drying to obtain a composite powder;

[0010] 4) The obtained composite powder and Si powder are uniformly dispersed in a polar solvent to obtain an aerosol precursor solution, which is then atomized and microwave treated, and then dried and calcined to obtain the metal-doped Cu-Si based catalyst.

[0011] In the above scheme, the copper salt can be selected from one or more of copper sulfate, copper chloride, copper nitrite, copper acetate, copper nitrate, copper oxalate, copper phosphate, copper formate, copper oxalate, copper phthalate, bis(diethyl)copper phosphate, dimethoxycopper, and diethoxycopper.

[0012] In the above scheme, the metal auxiliary salt is one or more soluble inorganic salts or organic salts of metal M, wherein M is selected from one or more of Ni, Zn, Zr, Al, Fe, Mn, Co, Mo, Cr, Mg, W, Sn, Ga, In, La, Pr, Ce, Ru, Rh, Pd, Au, Ag, and Pt.

[0013] Preferably, the soluble inorganic salt of M is selected from one or more of nitrate, chloride and sulfate of M.

[0014] Preferably, the soluble organic salt of M is selected from acetate or oxalate of M.

[0015] In the above scheme, in the composite metal salt solution, the concentration of copper salt is 1-50wt%, and the concentration of metal auxiliary salt is 1-20wt%.

[0016] In the above scheme, the polar solvent used in step 1) is one or more of water, methanol, ethanol, etc., preferably water.

[0017] In the above scheme, the preparation steps of the composite metal salt solution include: dissolving the copper salt in part of the solvent, and ultrasonically stirring (0.5-6h) to form a clear and transparent solution; then dissolving the metal auxiliary salt in part of the solvent, adding it to the clear and transparent solution, and ultrasonically stirring (0.5-6h) to form a clear and transparent solution.

[0018] In the above scheme, the non-polar organic solvent used in step 2) is one or more of benzene, toluene, chloroform, carbon tetrachloride, petroleum ether, ethyl acetate, ethylene dichloride, xylene, etc.; the surfactant is one or more of stearic acid, sodium dodecylbenzenesulfonate, alkyl glucoside (APG), fatty acid glyceride, fatty acid sorbitan (Span), polysorbate (Tween), sodium hexadecylbenzenesulfonate, hexadecyltrimethylammonium bromide, etc.

[0019] In the above scheme, the mass ratio of the polar solvent, the non-polar organic solvent and the surfactant introduced in step 2) is 1:0.1-10:0.001-0.5.

[0020] In the above scheme, the freezing treatment step uses a cold bath pot or a freeze dryer to freeze at -40 to -80°C for 1 to 24 hours.

[0021] In the above scheme, the carbon source precursor can be selected from one of glucose, starch, fructose, lactose and the like.

[0022] In the above scheme, the mass ratio of the introduced copper salt and carbon source precursor is 1:1-120.

[0023] In the above scheme, the solid-liquid ratio of the carbon source precursor introduced in step 3) to the microemulsion is 1g:0.8-10ml.

[0024] In the above scheme, the temperature used for the azeotropic distillation reaction in step 3) is 70-150° C. and the time is 24-144 h.

[0025] In the above scheme, the mass ratio of the composite powder to the Si powder in step 4) is 1:0.1-10.

[0026] In the above scheme, the silicon powder is commercial silicon powder, and the size of the silicon powder is 20-60nm, 60-100nm, 100-200nm, 200-500nm, 500-1000nm or 1000-3000nm, preferably 100-200nm.

[0027] In the above scheme, the dispersion step in step 4) includes: stirring for 0.5-6 hours, and then ultrasonicating for 0.5-6 hours.

[0028] In the above scheme, the polar solvent in step 4) is one or more of water, methanol, ethanol, etc.

[0029] In the above scheme, the concentration of Si powder in the aerosol precursor solution is 1-50wt%.

[0030] In the above scheme, the particle size of the aerosol droplets formed by atomization is 0.1-100 μm.

[0031] In the above scheme, the pressure used in the atomization step is 0.01-0.5MPa and the flow rate is 5-100mL / min.

[0032] In the above scheme, the power used for the microwave treatment is 200-1000W and the time is 0.5-30min.

[0033] In the above scheme, the temperature used in the drying step is 300-1000° C. and the time is 10-600s.

[0034] In the above scheme, the temperature used in the calcination step is 400-1000°C and the time is 0.5-24h.

[0035] Furthermore, the introduced Cu element accounts for 0.01-50% of the mass of the Si powder, preferably 20-30%.

[0036] Furthermore, the introduced M element accounts for 0.01-50% by mass of the Si powder, preferably 20-30% by mass.

[0037] In the above scheme, the microemulsion system formed in step 2) is an oil-in-water reverse microemulsion system, comprising a polar solvent and a non-polar solvent, wherein the polar solvent is one of water, methanol, and ethanol or any mixture thereof, and the non-polar organic solvent is one of benzene, toluene, chloroform, carbon tetrachloride, petroleum ether, ethyl acetate, dichloroethane, and xylene, and these organic solvents can form azeotropes with water.

[0038] The metal-doped Cu-Si-based catalyst prepared according to the above scheme has a flower-like high-porosity spherical structure, which is conducive to exposing more active sites. Its particle size is 0.5-2μm and has good dispersibility; the Si powder matrix is ​​loaded with uniformly distributed copper oxides and metal additive oxides.

[0039] The present invention also provides a method for preparing trichlorosilane by using a metal-doped Cu-Si based catalyst, comprising the following steps: using Si and HCl as raw materials, using a metal-doped Cu-Si based catalyst for a catalytic reaction, wherein the amount of the catalyst used accounts for 5-20% of the molar amount of HCl introduced in the synthesis of trichlorosilane, the catalytic reaction temperature is 200-280° C., and the catalytic reaction is carried out at 0.1-2 MPa to obtain trichlorosilane.

[0040] In the above scheme, the catalytic reaction time is 2-24h.

[0041] In the above scheme, the catalytic reaction device is a fixed bed or a fluidized bed.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] 1) The present invention adopts aerosol evaporation self-assembly technology based on microemulsion freeze drying, azeotropic distillation coupled with microwave-assisted process, which can achieve in-situ loading and highly uniform dispersion of Cu element and doped metal elements on Si powder;

[0044] 2) The present invention first adopts freeze drying and azeotropic distillation process, forms azeotropes through non-polar organic solvent and polar solvent phase, metal salt is uniformly dissolved and dispersed in polar solvent and compounded in the form of metal ions, then mixed with non-polar organic solvent, surfactant and auxiliary agent to form microemulsion, freeze drying and azeotropic distillation are carried out to promote uniform compounding of metal ions and dry to form composite powder; then the aerosol precursor solution is prepared by ultrasonically dispersing it and silicon powder in polar solution, atomizing to form aerosol droplets with wide distribution of several nanometers to tens of microns, and combining microwave treatment and heating and drying treatment means to promote the effective loading and highly uniform dispersion of Cu element and doped metal element on Si powder, and prepare Cu-Si based catalyst doped with auxiliary metal M, which is applied to prepare trichlorosilane, which helps to reduce the catalytic reaction temperature, reduce the amount of catalyst, improve the reaction selectivity, and improve the yield of trichlorosilane;

[0045] 3) The preparation process involved in the present invention is relatively simple, has a large output, can be mass-produced, has a short preparation cycle, is conducive to improving the conversion rate of trichlorosilane synthesis reaction, and can provide a new idea for the preparation of high-performance trichlorosilane catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 Schematic diagram of the preparation process of self-assembled materials by azeotropic distillation coupled with aerosol evaporation.

[0047] Figure 2 This is the XRD pattern of the metal-doped Cu-Si based catalyst obtained in Example 1.

[0048] Figure 3 These are SEM images of the metal-doped Cu-Si based catalyst obtained in Example 1 at different magnifications.

[0049] Figure 4 This is the mapping diagram of the metal-doped Cu-Si based catalyst obtained in Example 1.

[0050] Figure 5 This is the EDS image of the metal-doped Cu-Si based catalyst obtained in Example 1.

[0051] Figure 6 This is the SEM image of the metal-doped Cu-Si based catalyst obtained in Example 2.

[0052] Figure 7 This is the SEM image of the metal-doped Cu-Si based catalyst obtained in Example 3. DETAILED DESCRIPTION

[0053] The present invention is further described below in conjunction with specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0054] Example 1

[0055] A method for preparing a metal-doped Cu-Si based catalyst comprises the following steps:

[0056] 1) Weigh 1.506 g of copper nitrate trihydrate and dissolve it in 50 mL of deionized water, ultrasonicate for 1 hour and stir for 1 hour to form a uniform blue clear copper salt solution; weigh 1.981 g of nickel nitrate hexahydrate and dissolve it in 50 mL of deionized water, ultrasonicate for 1 hour and stir for 1 hour to form a uniform green clear metal additive salt solution, add it to the prepared copper salt solution, and mix well to obtain a composite metal salt solution;

[0057] 2) Pour part of the composite metal salt solution into a flask, pour in benzene, add 5g of hexadecyltrimethylammonium bromide as a surfactant, and control the mass ratio of the introduced water, benzene, and surfactant to be 1:2:0.3, stir for 6 hours, and form a microemulsion; put the obtained microemulsion into a closed container and put it into a cold bath pot or a freeze dryer, and freeze it at -80°C for 12 hours;

[0058] 3) 3 g of glucose was added to the frozen microemulsion (30 mL), and the azeotropic distillation reaction was carried out for 24 h (temperature was 75° C.). After the reaction, the sample was taken out, washed with ethanol and centrifuged, and then the sample was freeze-dried to form a composite powder;

[0059] 4) Weigh Si powder and the obtained composite powder in a mass ratio of 0.2:1, and use ethanol for ultrasonic dispersion. After stirring for 4 hours, continue ultrasonication for 1 hour to form a uniformly dispersed dispersion, i.e., an aerosol precursor solution (the concentration of Si powder is 5wt%); transfer it to an atomizer with an atomization pressure of 0.1MPa and a flow rate of 30mL / min. After atomizing the dispersion under nitrogen flow conditions, transfer it to a microwave generator with a microwave power of 700W and a microwave time of 30s. Transfer it to a tubular furnace with the air flow for high-temperature treatment. The temperature of the tubular furnace is 600°C, the air flow rate is 50mL / min, and the treatment time is 20s; use a tail powder collection device (70°C) to collect the powder, place the powder in a muffle furnace, and calcine it at 400°C for 3h. The collected powder is a Ni-doped Cu-Si based catalyst.

[0060] Figure 2 This is the XRD pattern of the catalyst obtained in this example. It can be seen that the prepared Ni-Cu bimetallic Si catalyst presents a good crystal structure, which contains silicon, CuO and NiO.

[0061] Figure 3 From the SEM image of the catalyst obtained in this example, it can be seen that the catalyst particle size is about 1-2 μm, with a flower-like high-porosity spherical structure, and the particle size is uniform and the dispersion is high.

[0062] Figure 4 This is the mapping diagram of the catalyst obtained in this example. It can be seen that in the obtained catalyst, Si, Ni, and Cu elements are dispersed very evenly, indicating that the catalyst prepared by this method can achieve high dispersion of composite metal elements.

[0063] Figure 5 This is the EDS image of the catalyst obtained in this example. It can be clearly seen that the contents of Cu and Ni are consistent with the added amounts. The relative content of Cu (relative to the total mass of the catalyst, the same below) is 19.32%, and the relative content of Ni is 19.45%.

[0064] The catalyst obtained in this example is applied to prepare trichlorosilane from HCl, and the specific preparation steps are as follows:

[0065] The catalyst was pressed into tablets and sieved, and placed in a fixed bed (reactor inner diameter 20 mm, tube length 50 cm) (the amount of catalyst accounted for 5% of the molar amount of introduced HCl), purged with N2 for 1 h, the temperature was raised to 200°C, HCl was introduced, the flow rate was set to 15 mL / min, the reaction pressure was 0.1 MPa, the reaction time was 4 h, the product after the reaction was condensed by a condenser and collected with toluene, the remaining gas was collected with an alkaline liquid and then emptied, the collected mixed solution was fixed to volume and quantitatively analyzed by gas chromatography (Agilent 8890, DB-1 chromatographic column, TCD detector), the trichlorosilane content in the obtained product was 92.31%, and the conversion rate calculated based on the Si content was 42.31%.

[0066] Example 2

[0067] A method for preparing a metal-doped Cu-Si based catalyst comprises the following steps:

[0068] 1) Weigh 0.753 g of copper nitrate trihydrate and dissolve it in 30 mL of deionized water, ultrasonicate for 1 hour and stir for 1 hour to form a uniform blue clear copper salt solution; weigh 1.390 g of aluminum nitrate nonahydrate and dissolve it in 50 mL of deionized water, ultrasonicate for 1 hour and stir for 1 hour to form a transparent and clear metal additive salt solution, add the copper salt solution to the obtained metal additive salt solution, ultrasonicate for 1 hour and stir for 1 hour to form a uniform composite metal salt solution;

[0069] 2) Pour part of the composite metal salt solution into a flask, pour in benzene, add 5g of stearic acid as a surfactant, and control the mass ratio of introduced water, benzene, and surfactant to be 1:3:0.1, stir for 4 hours to form a microemulsion; put the obtained microemulsion into a closed container and put it into a cold bath pot or a freeze dryer, and freeze it at a temperature of -40°C for 6 hours;

[0070] 3) 5 g of glucose was added to the frozen microemulsion (50 ml), and the reaction was carried out by azeotropic distillation for 24 h (temperature was 80° C.). After the reaction was completed, the sample was taken out, washed with ethanol and centrifuged, and then the sample was freeze-dried to form a composite powder;

[0071] 4) Weigh Si powder and the obtained composite powder in a mass ratio of 0.2:1, and use ethanol for ultrasonic dispersion. After stirring for 4 hours, continue ultrasonication for 1 hour to form a uniformly dispersed dispersion, i.e., an aerosol precursor solution (the concentration of Si powder is 10%); transfer it to an atomizer with an atomization pressure of 0.1 MPa and a flow rate of 20 mL / min, transfer it to an atomizer, atomize the dispersion under nitrogen flow conditions, and then transfer it to a microwave generator with a microwave power of 600 W and a microwave time of 40 s. Transfer it to a tubular furnace with the air flow for high-temperature treatment. The temperature of the tubular furnace is 800°C, the air flow rate is 100 mL / min, and the treatment time is 15 s; use a tail powder collection device (70°C) to collect the powder, place the powder in a muffle furnace, and calcine it at 400°C for 3 hours. The collected powder is the Ni-doped Cu-Si catalyst.

[0072] After testing, the catalyst particle size obtained in this example is about 1-2 μm (see Figure 6 ), the relative content of Cu is 10.12%, and the relative content of Al is 4.92%.

[0073] The catalyst obtained in this example is applied to prepare trichlorosilane from HCl, and the specific preparation steps are as follows:

[0074] The catalyst is used to prepare trichlorosilane. The catalyst is pressed into tablets and then sieved, and placed in a fixed bed (reactor inner diameter 20 mm, tube length 50 cm) (the amount of catalyst used accounts for 8% of the molar amount of introduced HCl), purged with N2 for 1 hour, the temperature is raised to 200°C, HCl is introduced, the flow rate is set to 15 mL / min, the reaction pressure is 0.5 MPa, the reaction time is 4 hours, the product after the reaction is condensed by a condenser and collected with toluene, the remaining gas is collected with an alkaline liquid and then emptied, the collected mixed solution is fixed to volume and then quantitatively analyzed by gas chromatography (Agilent 8890, DB-1 chromatographic column, TCD detector), the trichlorosilane content in the obtained product is 81.11%, and the conversion rate calculated based on the Si content is 35.15%.

[0075] Example 3

[0076] A method for preparing a metal-doped Cu-Si based catalyst comprises the following steps:

[0077] 1) Weigh 0.753 g of copper nitrate trihydrate and dissolve it in 30 mL of deionized water, ultrasonicate for 1 hour and stir for 1 hour to form a uniform blue clear copper salt solution; weigh 0.350 g of zirconium nitrate pentahydrate and dissolve it in 50 mL of deionized water, ultrasonicate for 1 hour and stir for 1 hour to form a transparent and clear metal additive salt solution, add the copper salt solution to the obtained metal additive salt solution, ultrasonicate for 1 hour and stir for 1 hour to form a uniform composite metal salt solution;

[0078] 2) Pour part of the composite metal salt solution into a flask, pour in benzene, add 6g of sodium dodecyl sulfate as a surfactant, and control the mass ratio of the introduced water, benzene, and surfactant to be 1:2:0.1, stir for 6 hours to form a microemulsion; put the obtained microemulsion into a closed container and put it into a cold bath pot or a freeze dryer, and freeze it at a temperature of -40°C for 24 hours;

[0079] 3) 10 g of glucose was added to the frozen microemulsion (10 mL), and the reaction was carried out by azeotropic distillation for 24 h (temperature was 70° C.). After the reaction was completed, the sample was taken out, washed with ethanol and centrifuged, and then the sample was freeze-dried to form a composite powder;

[0080] 4) Weigh Si powder and the obtained composite powder in a mass ratio of 0.2:1, and use ethanol for ultrasonic dispersion. After stirring for 4 hours, continue ultrasonication for 1 hour to form a uniformly dispersed dispersion, i.e., an aerosol precursor solution (the concentration of Si powder is 15%); transfer the uniformly dispersed precursor solution to an atomizer, the atomization pressure is 0.1 MPa, the flow rate is 35 mL / min, the dispersion is atomized under nitrogen flow conditions, and then transferred to a microwave generator, the microwave power is 1000 W, the microwave time is 30S, and it is transferred to a tubular furnace with the airflow for high-temperature treatment, the tubular furnace temperature is 600°C, and the airflow rate is 50 mL / min; the powder is collected by a tail powder collection device (70°C), and the powder is placed in a muffle furnace and calcined at 400°C for 3 hours. The collected powder is the Zr-doped Cu-Si catalyst.

[0081] After testing, the catalyst particle size obtained in this example is about 1-2 μm (see Figure 7 ), the relative content of Cu is 9.86%, and the relative content of Zr is 4.87%.

[0082] The catalyst obtained in this example is applied to prepare trichlorosilane from HCl, and the specific preparation steps are as follows:

[0083] The method for preparing trichlorosilane using a catalyst is as follows: the catalyst is pressed into tablets and then sieved, and placed in a fixed bed (reactor inner diameter 20 mm, tube length 50 cm) (the amount of the catalyst accounts for 7% of the molar amount of the introduced HCl), N2 is used for purging for 1 hour, the temperature is raised to 250° C., HCl is introduced, the flow rate is set to 15 mL / min, the reaction pressure is 1 MPa, the reaction time is 4 hours, the product after the reaction is condensed by a condenser and then collected with toluene, the remaining gas is collected with an alkaline liquid and then emptied, the collected mixed solution is fixed to volume and then quantitatively analyzed by gas chromatography (Agilent 8890, DB-1 chromatographic column, TCD detector), the trichlorosilane content in the obtained product is 80.12%, and the conversion rate calculated based on the Si content is 31.32%.

[0084] Example 4

[0085] A method for preparing a metal-doped Cu-Si based catalyst comprises the following steps:

[0086] 1) Weigh 0.753 g of copper nitrate trihydrate and dissolve it in 30 mL of deionized water, ultrasonicate for 1 hour and then stir for 1 hour to form a uniform blue clear copper salt solution; weigh 0.579 g of zirconium nitrate pentahydrate and dissolve it in 50 mL of deionized water, ultrasonicate for 1 hour and then stir for 1 hour to form a transparent and clear metal additive salt solution, add the copper salt solution to the obtained metal additive salt solution, ultrasonicate for 1 hour and then stir for 1 hour to form a uniform composite metal salt solution;

[0087] 2) Pour part of the composite metal salt solution into a flask, pour in chloroform, add 1 g of fatty acid glyceride as a surfactant, and control the mass ratio of the introduced water, chloroform, and surfactant to be 1:5:0.1, stir for 10 hours to form a microemulsion; put the obtained microemulsion into a closed container and put it into a cold bath pot or a freeze dryer, and freeze it at a temperature of -40°C for 12 hours;

[0088] 3) 5 g of glucose was added to the frozen microemulsion (20 mL), and the azeotropic distillation reaction was carried out for 24 h (temperature was 100° C.). After the reaction was completed, the sample was taken out, washed with ethanol and centrifuged, and then the sample was freeze-dried to form a composite powder;

[0089] 4) Weigh Si powder and the obtained composite powder in a mass ratio of 0.2:1, and use ethanol for ultrasonic dispersion. After stirring for 4 hours, continue ultrasonication for 1 hour to form a uniformly dispersed dispersion, i.e., an aerosol precursor solution (the concentration of Si powder is 10%); transfer it to an atomizer with an atomization pressure of 0.1 MPa and a flow rate of 30 mL / min; after atomizing the dispersion under nitrogen flow conditions, transfer it to a microwave generator with a microwave power of 800 W and a microwave time of 40 s, and transfer it to a tubular furnace with the air flow for high-temperature treatment. The temperature of the tubular furnace is 600°C and the air flow rate is 100 mL / min; use a tail powder collection device (70°C) to collect the powder, and place the powder in a muffle furnace and calcine it at 400°C for 3 hours. The collected powder is the Zr-doped Cu-Si catalyst.

[0090] According to the test, the catalyst particle size obtained in this embodiment is about 1-2 μm, the relative content of Cu is 9.86%, and the relative content of Zr is 9.73%.

[0091] The catalyst obtained in this example is applied to prepare trichlorosilane from HCl, and the specific preparation steps are as follows:

[0092] The catalyst is used to prepare trichlorosilane. The catalyst is pressed into tablets and then sieved, and placed in a fixed bed (reactor inner diameter 20 mm, tube length 50 cm) (the amount of catalyst used accounts for 10% of the molar amount of introduced HCl), purged with N2 for 1 hour, the temperature is raised to 240°C, HCl is introduced, the flow rate is set to 15 mL / min, the reaction pressure is 1 MPa, the reaction time is 4 hours, the product after the reaction is condensed by a condenser and collected with toluene, the remaining gas is collected with an alkaline liquid and then emptied, the collected mixed solution is fixed to volume and then quantitatively analyzed by gas chromatography (Agilent 8890, DB-1 chromatographic column, TCD detector), the trichlorosilane content in the obtained product is 82.41%, and the conversion rate calculated based on the Si content is 21.35%.

[0093] Example 5

[0094] A method for preparing a metal-doped Cu-Si based catalyst comprises the following steps:

[0095] 1) Weigh 1.506 g of copper nitrate trihydrate and dissolve it in 30 mL of deionized water, ultrasonicate for 1 hour and then stir for 1 hour to form a uniform blue clear copper salt solution; weigh 0.721 g of ferric nitrate nonahydrate and dissolve it in 50 mL of deionized water, ultrasonicate for 1 hour and then stir for 1 hour to form a transparent and clear metal additive salt solution, add the copper salt solution to the obtained metal additive salt solution, ultrasonicate for 1 hour and then stir for 1 hour to form a uniform composite metal salt solution;

[0096] 2) Pour part of the composite metal salt solution into a flask, pour carbon tetrachloride into it, add 6g of sodium hexadecyl sulfate as a surfactant, and control the mass ratio of the introduced water, carbon tetrachloride, and surfactant to be 1:1:0.5, stir for 6 hours to form a microemulsion; put the obtained microemulsion into a closed container and put it into a cold bath pot or a freeze dryer, and freeze it at a temperature of -40°C for 24 hours;

[0097] 3) 5 g of glucose was added to the frozen microemulsion (16 mL), and the azeotropic distillation reaction was carried out for 24 h (temperature was 100° C.). After the reaction was completed, the sample was taken out, washed with ethanol and centrifuged, and then the sample was freeze-dried to form a composite powder;

[0098] 4) Weigh Si powder and the obtained composite powder in a mass ratio of 0.2:1, and use ethanol for ultrasonic dispersion. After stirring for 4 hours, continue ultrasonication for 1 hour to form a uniformly dispersed dispersion, i.e., an aerosol precursor solution (the concentration of Si powder is 12%); transfer it to an atomizer with an atomization pressure of 0.1 MPa and a flow rate of 50 mL / min; after atomizing the dispersion under nitrogen flow conditions, transfer it into a microwave generator with a microwave power of 900 W and a microwave time of 20 s, and transfer it to a tubular furnace with the air flow for high-temperature treatment. The temperature of the tubular furnace is 800°C and the air flow rate is 100 mL / min; collect the powder using a tail powder collection device (70°C), place the powder in a muffle furnace, and calcine it at 400°C for 3 hours. The collected powder is the Fe-doped Cu-Si catalyst.

[0099] According to the test, the catalyst particle size obtained in this embodiment is about 1-2 μm, the relative content of Cu is 19.63%, and the relative content of Fe is 4.86%.

[0100] The catalyst obtained in this example is applied to prepare trichlorosilane from HCl, and the specific preparation steps are as follows:

[0101] The catalyst was pressed into tablets and sieved, and placed in a fixed bed (reactor inner diameter 20 mm, tube length 50 cm) (the amount of catalyst accounted for 5% of the molar amount of introduced HCl), purged with N2 for 1 h, the temperature was raised to 280°C, HCl was introduced, the flow rate was set to 15 mL / min, the reaction pressure was 1 MPa, the reaction time was 4 h, the product after the reaction was condensed by a condenser and collected with toluene, the remaining gas was collected with an alkaline liquid and then emptied, the collected mixed solution was fixed to volume and quantitatively analyzed by gas chromatography (Agilent 8890, DB-1 chromatographic column, TCD detector), the trichlorosilane content in the obtained product was 85.42%, and the conversion rate calculated based on the Si content was 36.34%.

[0102] Example 6

[0103] A method for preparing a metal-doped Cu-Si based catalyst comprises the following steps:

[0104] 1) Weigh 1.506 g of copper nitrate trihydrate and dissolve it in 30 mL of deionized water, ultrasonicate for 1 hour and then stir for 1 hour to form a uniform blue clear copper salt solution; weigh 0.721 g of ferric nitrate nonahydrate and dissolve it in 50 mL of deionized water, ultrasonicate for 1 hour and then stir for 1 hour to form a transparent and clear metal additive salt solution, add the copper salt solution to the obtained metal additive salt solution, ultrasonicate for 1 hour and then stir for 1 hour to form a uniform composite metal salt solution;

[0105] 2) Pour part of the composite metal salt solution into a flask, pour petroleum ether into it, add 6g of sodium dodecyl sulfate as a surfactant, and control the mass ratio of the introduced water, petroleum ether, and surfactant to be 1:3:0.4, and stir for 6 hours to form a microemulsion; put the obtained microemulsion into a closed container and put it into a cold bath pot or a freeze dryer, and freeze it at a temperature of -40°C for 24 hours;

[0106] 3) 5 g of glucose was added to the frozen microemulsion, and the reaction was carried out by azeotropic distillation for 24 h (temperature was 80° C.). After the reaction was completed, the sample was taken out, washed with ethanol and centrifuged, and then the sample was freeze-dried to form a composite powder;

[0107] 4) Weigh Si powder and the obtained composite powder in a mass ratio of 0.2:1, and use ethanol for ultrasonic dispersion. After stirring for 4 hours, continue ultrasonication for 1 hour to form a uniformly dispersed dispersion, i.e., an aerosol precursor solution; transfer it to an atomizer with an atomization pressure of 0.1 MPa and a flow rate of 10 mL / min; after atomizing the dispersion under nitrogen flow conditions, transfer it into a microwave generator with a microwave power of 700 W and a microwave time of 10 s, and transfer it to a tubular furnace with the air flow for high-temperature treatment. The temperature of the tubular furnace is 800°C and the air flow rate is 100 mL / min; collect the powder using a tail powder collection device (70°C), place the powder in a muffle furnace, and calcine it at 400°C for 3 hours. The collected powder is the Fe-doped Cu-Si catalyst.

[0108] After testing, the catalyst obtained in this example has a particle size of about 1-2 μm, a relative content of Cu of 19.63%, and a relative content of Fe of 4.86%, and is used to prepare trichlorosilane from HCl.

[0109] The catalyst obtained in this example is applied to prepare trichlorosilane from HCl, and the specific preparation steps are as follows:

[0110] The catalyst was pressed into tablets and sieved, and placed in a fixed bed (reaction inner diameter 20 mm, tube length 50 cm) (the amount of catalyst accounted for 6% of the molar amount of introduced HCl), purged with N2 for 1 h, the temperature was raised to 280°C, HCl was introduced, the flow rate was set to 15 mL / min, the reaction pressure was 1 MPa, the reaction time was 4 h, the product after the reaction was condensed by a condenser and collected with toluene, the remaining gas was collected with an alkaline liquid and then emptied, the collected mixed solution was fixed to volume and quantitatively analyzed by gas chromatography (Agilent 8890, DB-1 chromatographic column, TCD detector), the trichlorosilane content in the obtained product was 85.37%, and the conversion rate calculated based on the Si content was 32.57%.

[0111] Example 7

[0112] A method for preparing a metal-doped Cu-Si based catalyst comprises the following steps:

[0113] 1) Weigh 1.506 g of copper nitrate trihydrate and dissolve it in 30 mL of deionized water, ultrasonicate for 1 hour and then stir for 1 hour to form a uniform blue clear copper salt solution; weigh 0.157 g of silver nitrate and dissolve it in 50 mL of deionized water, ultrasonicate for 1 hour and then stir for 1 hour to form a transparent and clear metal additive salt solution, add the copper salt solution to the obtained metal additive salt solution, ultrasonicate for 1 hour and then stir for 1 hour to form a uniform composite metal salt solution;

[0114] 2) Pour part of the composite metal salt solution into a flask, pour in ethyl acetate, add 6g of sodium dodecyl sulfate as a surfactant, and control the mass ratio of the introduced water, ethyl acetate, and surfactant to be 1:2:0.6 and stir for 6 hours to form a microemulsion; put the obtained microemulsion into a closed container and put it into a cold bath pot or a freeze dryer, and freeze it at a temperature of -40°C for 24 hours;

[0115] 3) 10 g of glucose was added to the frozen microemulsion (13 mL), and the reaction was carried out by azeotropic distillation for 24 h (temperature was 70° C.). After the reaction was completed, the sample was taken out, washed with ethanol and centrifuged, and then the sample was freeze-dried to form a composite powder;

[0116] 4) Weigh Si powder and the obtained composite powder in a mass ratio of 0.2:1, and use ethanol for ultrasonic dispersion. After stirring for 4 hours, continue ultrasonication for 1 hour to form a uniformly dispersed dispersion, i.e., an aerosol precursor solution (the concentration of Si powder is 15wt%); transfer it to an atomizer with an atomization pressure of 0.2MPa and a flow rate of 15mL / min. After atomizing the dispersion under nitrogen flow conditions, transfer it to a microwave generator with a microwave power of 700W and a microwave time of 10S. Transfer it to a tubular furnace with the air flow for high-temperature treatment. The temperature of the tubular furnace is 800°C and the air flow rate is 100mL / min. Use a tail powder collection device (70°C) to collect the powder, place the powder in a muffle furnace, and calcine it at 400°C for 3h. Collect the powder to obtain an Ag-doped Cu-Si catalyst.

[0117] After testing, the catalyst obtained in this example has a particle size of about 1-2 μm, a relative content of Cu of 19.87%, and a relative content of Ag of 4.86%, and is used to prepare trichlorosilane from HCl.

[0118] The catalyst obtained in this example is applied to prepare trichlorosilane from HCl, and the specific preparation steps are as follows:

[0119] The catalyst was pressed into tablets and sieved, and placed in a fixed bed (reaction inner diameter 20 mm, tube length 50 cm) (the amount of catalyst accounted for 10% of the molar amount of introduced HCl), purged with N2 for 1 h, the temperature was raised to 280°C, HCl was introduced, the flow rate was set to 15 mL / min, the reaction pressure was 1 MPa, the reaction time was 4 h, the product after the reaction was condensed by a condenser and collected with toluene, the remaining gas was collected with an alkaline liquid and then emptied, the collected mixed solution was fixed to volume and quantitatively analyzed by gas chromatography (Agilent 8890, DB-1 chromatographic column, TCD detector), the trichlorosilane content in the obtained product was 73.25%, and the conversion rate calculated based on the Si content was 30.15%.

[0120] Example 8

[0121] A method for preparing a metal-doped Cu-Si based catalyst comprises the following steps:

[0122] 1) Weigh 1.506 g of copper nitrate trihydrate and dissolve it in 30 mL of deionized water, ultrasonicate for 1 hour and then stir for 1 hour to form a uniform blue clear copper salt solution; weigh 0.505 g of silver nitrate and dissolve it in 50 mL of deionized water, ultrasonicate for 1 hour and then stir for 1 hour to form a transparent and clear metal additive salt solution, add the copper salt solution to the obtained metal additive salt solution, ultrasonicate for 1 hour and then stir for 1 hour to form a uniform composite metal salt solution;

[0123] 2) Pour part of the composite metal salt solution into a flask, pour in dichloroethane, add 6g of sodium dodecyl sulfate as a surfactant, and control the mass ratio of the introduced water, dichloroethane, and surfactant to be 1:3:0.8 and stir for 6 hours to form a microemulsion; put the obtained microemulsion into a closed container and put it into a cold bath pot or a freeze dryer, and freeze it at a temperature of -40°C for 24 hours;

[0124] 3) 10 g of glucose was added to the frozen microemulsion (9 mL), and the reaction was carried out by azeotropic distillation for 24 h (temperature was 105° C.). After the reaction was completed, the sample was taken out, washed with ethanol and centrifuged, and then the sample was freeze-dried to form a composite powder;

[0125] 4) Weigh Si powder and the obtained composite powder in a mass ratio of 0.2:1, and use ethanol for ultrasonic dispersion. After stirring for 4 hours, continue ultrasonication for 1 hour to form a uniformly dispersed dispersion, i.e., an aerosol precursor solution (the concentration of Si powder is 7wt%); transfer it to an atomizer with an atomization pressure of 0.2MPa and a flow rate of 18mL / min. After atomizing the dispersion under nitrogen flow conditions, transfer it to a microwave generator with a microwave power of 800W and a microwave time of 9s. Transfer it to a tubular furnace with the air flow for high-temperature treatment. The temperature of the tubular furnace is 800°C and the air flow rate is 100mL / min. Use a tail powder collection device (70°C) to collect the powder, place the powder in a muffle furnace, and calcine it at 400°C for 3h. The collected powder is the Ce-doped Cu-Si catalyst.

[0126] According to the test, the catalyst particle size obtained in this embodiment is about 1-2 μm, the relative content of Cu is 19.87%, and the relative content of Ce is 4.86%.

[0127] The catalyst obtained in this example is applied to prepare trichlorosilane from HCl, and the specific preparation steps are as follows:

[0128] The catalyst was pressed into tablets and sieved, and placed in a fixed bed (reaction inner diameter 20 mm, tube length 50 cm) (catalyst accounts for 8% of HCl), purged with N2 for 1 hour, the temperature was raised to 260°C, HCl was introduced, the flow rate was set to 15 mL / min, the reaction pressure was 1 MPa, the reaction time was 4 hours, the product after the reaction was condensed by a condenser and collected with toluene, the remaining gas was collected with an alkaline liquid and then emptied, the collected mixed solution was fixed to volume and quantitatively analyzed by gas chromatography (Agilent 8890, DB-1 chromatographic column, TCD detector), the trichlorosilane content in the obtained product was 83.25%, and the conversion rate calculated based on the Si content was 40.36%.

[0129] Example 9

[0130] A method for preparing a metal-doped Cu-Si based catalyst comprises the following steps:

[0131] 1) Weigh 1.506 g of copper nitrate trihydrate and dissolve it in 30 mL of deionized water, ultrasonicate for 1 hour and stir for 1 hour to form a uniform blue clear copper salt solution; weigh 0.021 g of ruthenium acetate and dissolve it in 50 mL of deionized water, ultrasonicate for 1 hour and stir for 1 hour to form a transparent and clear metal additive salt solution, add the copper salt solution to the obtained metal additive salt solution, ultrasonicate for 1 hour and stir for 1 hour to form a uniform composite metal salt solution;

[0132] 2) Pour part of the composite metal salt solution into a flask, pour in xylene, add 6g of sodium dodecyl sulfate as a surfactant, and control the mass ratio of the introduced water, xylene, and surfactant to be 1:4:0.9, stir for 6 hours to form a microemulsion; put the obtained microemulsion into a closed container and put it into a cold bath pot or a freeze dryer, and freeze it at a temperature of -40°C for 24 hours;

[0133] 3) 10 g of glucose was added to the frozen microemulsion (8 mL), and the reaction was carried out by azeotropic distillation for 24 h (temperature was 100° C.). After the reaction was completed, the sample was taken out, washed with ethanol and centrifuged, and then the sample was freeze-dried to form a composite powder;

[0134] 4) Weigh Si powder and the obtained composite powder in a mass ratio of 0.2:1, and use ethanol for ultrasonic dispersion. After stirring for 4 hours, continue ultrasonication for 1 hour to form a uniformly dispersed dispersion, i.e., an aerosol precursor solution (the concentration of Si powder is 5wt%); transfer it to an atomizer with an atomization pressure of 0.5MPa and a flow rate of 100mL / min. After atomizing the dispersion under nitrogen flow conditions, transfer it to a microwave generator with a microwave power of 900W and a microwave time of 12s. Transfer it to a tubular furnace with the air flow for high-temperature treatment. The temperature of the tubular furnace is 800°C and the air flow rate is 100mL / min. Use a tail powder collection device (70°C) to collect the powder, place the powder in a muffle furnace, and calcine it at 400°C for 3h. The collected powder is the Ru-doped Cu-Si catalyst.

[0135] According to the test, the catalyst particle size obtained in this embodiment is about 1-2 μm, the relative content of Cu is 19.87%, and the relative content of Ru is 0.98%.

[0136] The catalyst obtained in this example is applied to prepare trichlorosilane from HCl, and the specific preparation steps are as follows:

[0137] The catalyst was pressed into tablets and sieved, and placed in a fixed bed (reaction inner diameter 20 mm, tube length 50 cm) (the amount of catalyst accounted for 10% of the molar amount of introduced HCl), purged with N2 for 1 h, the temperature was raised to 240°C, HCl was introduced, the flow rate was set to 15 mL / min, the reaction pressure was 1 MPa, the reaction time was 4 h, the product after the reaction was condensed by a condenser and collected with toluene, the remaining gas was collected with an alkaline liquid and then emptied, the collected mixed solution was fixed to volume and quantitatively analyzed by gas chromatography (Agilent 8890, DB-1 chromatographic column, TCD detector), the trichlorosilane content in the obtained product was 86.11%, and the conversion rate calculated based on the Si content was 16.21%.

[0138] Comparative Example 1

[0139] A method for preparing a metal-doped Cu-Si based catalyst comprises the following steps:

[0140] 1) Weigh 1.506 g of copper nitrate trihydrate and dissolve it in 50 mL of deionized water, ultrasonicate for 1 hour and stir for 1 hour to form a uniform blue clear copper salt solution; weigh 1.981 g of nickel nitrate hexahydrate and dissolve it in 50 mL of deionized water, ultrasonicate for 1 hour and stir for 1 hour to form a uniform green clear metal additive salt solution, add it to the prepared copper salt solution, and mix well to obtain a composite metal salt solution;

[0141] 2) pouring the obtained composite metal salt solution into a flask, pouring benzene, adding 5g of hexadecyltrimethylammonium bromide as a surfactant, and controlling the mass ratio of the introduced water, benzene, and surfactant to be 1:2:0.3, stirring for 6 hours to form a microemulsion; placing the obtained microemulsion in a closed container and placing it in a cold bath pot or a freeze dryer, and freezing it at -80°C for 12 hours;

[0142] 3) adding 3 g of glucose to the frozen microemulsion, and subjecting to azeotropic distillation reaction for 24 h (temperature is 75° C.), taking out the sample after the reaction, washing with ethanol and centrifuging, and then freeze-drying the sample to form a composite powder;

[0143] 4) Weigh Si powder and the obtained composite powder in a mass ratio of 0.2:1, and use ethanol for ultrasonic dispersion. After stirring for 4 hours, continue ultrasonication for 1 hour to form a uniformly dispersed dispersion, i.e., an aerosol precursor solution; transfer it to an atomizer with an atomization pressure of 0.1 MPa and a flow rate of 30 mL / min. After the dispersion is atomized under nitrogen flow conditions, it is transferred to a tubular furnace with the airflow for high-temperature treatment. The tubular furnace temperature is 600°C, the airflow rate is 50 mL / min, and the treatment time is 20 s; the powder is collected using a tail powder collection device (70°C), and the powder is placed in a muffle furnace and calcined at 400°C for 3 hours. The collected powder is the Ni-doped Cu-Si based catalyst.

[0144] The catalyst obtained in this comparative example was applied to prepare trichlorosilane from HCl, and the specific preparation steps were as follows:

[0145] The catalyst was pressed into tablets and sieved, and placed in a fixed bed (reactor inner diameter 20 mm, tube length 50 cm) (the amount of catalyst accounted for 5% of the molar amount of introduced HCl), purged with N2 for 1 h, the temperature was raised to 200°C, HCl was introduced, the flow rate was set to 15 mL / min, the reaction pressure was 0.1 MPa, the reaction time was 4 h, the product after the reaction was condensed by a condenser and collected with toluene, the remaining gas was collected with an alkaline liquid and then emptied, the collected mixed solution was fixed to volume and quantitatively analyzed by gas chromatography (Agilent 8890, DB-1 chromatographic column, TCD detector), the trichlorosilane content in the obtained product was 50.12%, and the conversion rate calculated based on the Si content was 16.24%.

[0146] Comparative Example 2

[0147] A method for preparing a metal-doped Cu-Si based catalyst comprises the following steps:

[0148] 1) Weigh 1.506 g of copper nitrate trihydrate and dissolve it in 50 mL of deionized water, ultrasonicate for 1 hour and then stir for 1 hour to form a uniform blue clear copper salt solution; weigh 1.981 g of nickel nitrate hexahydrate and dissolve it in 50 mL of deionized water, ultrasonicate for 1 hour and then stir for 1 hour to form a uniform green clear metal additive salt solution, add it to the prepared copper salt solution, mix well to obtain a composite metal salt solution, dry the metal salt at 70-110° C. for 1-6 hours to obtain a composite metal salt powder;

[0149] 2) Weigh Si powder and the obtained composite powder in a mass ratio of 0.2:1, and use ethanol for ultrasonic dispersion. After stirring for 4 hours, continue ultrasonication for 1 hour to form a uniformly dispersed dispersion, i.e., an aerosol precursor solution; transfer it to an atomizer with an atomization pressure of 0.1 MPa and a flow rate of 30 mL / min. After the dispersion is atomized under nitrogen flow conditions, it is transferred into a microwave generator with a microwave power of 700 W and a microwave time of 30 seconds. It is then transferred to a tubular furnace with the airflow for high-temperature treatment. The temperature of the tubular furnace is 600°C, the airflow rate is 50 mL / min, and the treatment time is 20 seconds. The powder is collected using a tail powder collection device (70°C), and the powder is placed in a muffle furnace and calcined at 400°C for 3 hours. The collected powder is the NiCu-doped Si catalyst.

[0150] The catalyst obtained in this example is applied to prepare trichlorosilane from HCl, and the specific preparation steps are as follows:

[0151] The catalyst was pressed into tablets and sieved, and placed in a fixed bed (reactor inner diameter 20 mm, tube length 50 cm), purged with N2 for 1 h, the temperature was raised to 200°C, HCl was introduced, the flow rate was set to 15 mL / min, the reaction pressure was 0.1 MPa, the reaction time was 4 h, the product after the reaction was condensed by a condenser and collected with toluene, the remaining gas was collected with an alkaline liquid and then emptied, the collected mixed solution was fixed to volume and quantitatively analyzed by gas chromatography (Agilent 8890, DB-1 chromatographic column, TCD detector), the trichlorosilane content in the obtained product was 46.12%, and the conversion rate calculated based on the Si content was 19.34%.

[0152] In addition, the various embodiments of the present invention may be combined in any way, and as long as they do not violate the concept of the present invention, they shall also be regarded as the contents disclosed by the present invention. The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.

Claims

1. A method for preparing a metal-doped Cu-Si based catalyst, characterized in that: The following steps are involved: 1) uniformly mixing copper salt and metal auxiliary salt in a polar solvent to obtain a composite metal salt solution; 2) mixing the composite metal salt solution, the non-polar organic solvent and the surfactant uniformly to form a stable microemulsion system, and then freezing the system to obtain a stable microemulsion; 3) adding the carbon source precursor to the microemulsion obtained in step 2) to carry out azeotropic distillation reaction, and then washing and freeze-drying to obtain a composite powder; 4) The obtained composite powder and Si powder are uniformly dispersed in a polar solvent to obtain an aerosol precursor solution, which is then atomized and microwave treated, and then dried and calcined to obtain the metal-doped Cu-Si based catalyst.

2. The preparation method according to claim 1, characterized in that: The copper salt is one or more of copper sulfate, copper chloride, copper nitrite, copper acetate, copper nitrate, copper oxalate, copper phosphate, copper formate, copper oxalate, copper phthalate, bis(diethyl)copper phosphate, dimethoxycopper, and diethoxycopper; the metal additive salt is one or more of a soluble inorganic salt or organic salt of metal M, wherein M is selected from one or more of Ni, Zn, Zr, Al, Fe, Mn, Co, Mo, Cr, Mg, W, Sn, Ga, In, La, Pr, Ce, Ru, Rh, Pd, Au, Ag, and Pt.

3. The preparation method according to claim 1, characterized in that: In the composite metal salt solution, the concentration of copper salt is 5-50wt%, and the concentration of metal auxiliary salt is 1-20wt%.

4. The preparation method according to claim 1, characterized in that: The polar solvent used in step 1) is one or more of water, methanol and ethanol; the non-polar organic solvent used in step 2) is one or more of benzene, toluene, chloroform, carbon tetrachloride, petroleum ether, ethyl acetate, dichloroethane and xylene.

5. The preparation method according to claim 1, characterized in that: The surfactant is one or more of stearic acid, sodium dodecylbenzenesulfonate, alkyl glucoside, fatty acid glyceride, fatty acid sorbitan, polysorbate, sodium hexadecylbenzenesulfonate, and hexadecyltrimethylammonium bromide.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the polar solvent, the non-polar organic solvent and the surfactant introduced in step 2) is 1:0.1-10:0.001-0.

5.

7. The preparation method according to claim 1, characterized in that: The carbon source precursor is one of glucose, starch, fructose and lactose.

8. The preparation method according to claim 1, characterized in that: The introduced Cu element accounts for 0.01-50% of the mass of the Si powder; the introduced M element accounts for 0.01-50% of the mass of the Si powder.

9. The metal-doped Cu-Si based catalyst prepared by the preparation method according to any one of claim 1, characterized in that: It has a flower-like porous spherical structure, and the Si powder matrix is ​​loaded with evenly distributed copper oxides and metal additive oxides.

10. Use of the metal-doped Cu-Si based catalyst obtained by the preparation method according to any one of claims 1 to 8 or the metal-doped Cu-Si based catalyst according to claim 9 in preparing trichlorosilane.